Flexible self-repairing anti-cracking material with porous structure and preparation method of flexible self-repairing anti-cracking material
By constructing a closed microporous structure in a flexible polyurea elastomer SSPU, and using the reverse phase emulsion template method, the contradiction between crack resistance and flexibility of existing materials was solved, and the fracture energy and flexibility were significantly improved, and a soft but strong self-healing material was realized.
Patent Information
- Application Number
- CN202411493649.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
When existing flexible self-repair materials improve crack resistance, they often damage the material's flexibility and self-repair efficiency, and the fracture capacity is not enough to meet certain application needs.
The inverted emulsion template method was used to construct a closed microporous structure in a room temperature self-healing flexible polyurea elastomer SSPU. By changing the crack direction and stress distribution, the crack resistance and fracture energy of the material were significantly improved.
The crack resistance of the material is greatly improved without damaging the self-repair efficiency and flexibility of the material. The fracture energy can be as high as 100.86kJ m-2, an increase of 31.6 times. At the same time, the Young's modulus has significantly decreased and the flexibility has been improved.
Smart Images

Figure CN119529368A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials and relates to a flexible self-repairing anti-cracking material with a porous structure and a preparation method thereof. Background Art
[0002] Flexible polymer materials are crucial in various engineering applications such as wearable devices and soft robots. In these application scenarios, due to repeated stretching, bending and twisting during operation, high requirements are placed on the flexibility, large deformation and good fit of the materials. In order to extend the service life of the relevant materials, the ideal soft materials in these application scenarios should not only be able to spontaneously repair damage after damage, but also be able to resist crack propagation to prevent catastrophic failure due to crack propagation before damage repair in actual use. However, in the development of soft materials, self-healing and crack resistance are often conflicting requirements. Generally, replacing irreversible covalent bonds in soft polymer networks with weak supramolecular interactions can give materials self-healing functions without compromising inherent softness. However, in this low-energy network based on weak interchain supramolecular interactions, chemical bonds are more likely to break, so macroscopic cracks in polymers are also more likely to propagate. Therefore, the fracture energy of flexible self-healing materials (representing the critical energy required for crack propagation per unit area) is much lower than the fracture energy of covalently cross-linked polymers (such as rubber). In order to improve the crack resistance while maintaining the self-healing function to the greatest extent, a dual cross-linking strategy with two non-covalent interactions of different bonding strengths can be adopted. In these systems, the relatively weak interactions act as sacrificial bonds to increase the energy dissipation during material loading. However, the fracture energy of such materials is still low, usually in the range of 10–1000 J m -2 In order to further increase the fracture energy, covalent cross-linking, double networks, phase separation, crystal domains, nanocomposites and fibers are usually introduced into polymers. (Chem. Mater. 2018, 30, 6026; Phys. Rev. Lett. 2018, 121, 185501; Nat. Commun. 2021, 12, 1291; Proc. Natl. Acad. Sci. USA. 2020, 117, 7606) However, these methods have limited effects on the increase of fracture energy, and inevitably increase the hardness of the material and lose its flexibility, which is not conducive to emerging applications in soft electronics and robotics. (Nat. Electron. 2018, 1, 102; Nat. Mater. 2021, 20, 714) Summary of the invention
[0003] The purpose of the present invention is to provide a porous structured flexible self-healing anti-cracking material and a preparation method thereof. The method is a flexible material flexibility and toughening design, which uses an inverse emulsion template method to construct a closed microporous structure in a room temperature self-healing flexible polyurea elastomer SSPU, greatly improving the material's crack resistance without compromising the material's self-healing efficiency and flexibility. The prepared flexible porous self-healing material MPSPU has extremely high fracture energy and is suitable for various stretchable and functional devices.
[0004] The technical solution for achieving the purpose of the present invention is as follows:
[0005] The preparation method of the porous structured flexible self-repairing anti-cracking material comprises the following specific steps:
[0006] The room temperature self-healing flexible polyurea elastomer SSPU and the surfactant sodium dodecyl sulfate (SDS) are stirred and dissolved in chloroform at a mass ratio of 100:0.5-1.5 to obtain a viscous solution, and then water is added dropwise to the viscous solution at a mass ratio of water to the room temperature self-healing flexible polyurea elastomer SSPU of 50-150:100, and stirred until fully emulsified. The emulsion is then poured into a mold, left to stand at room temperature to allow the chloroform to evaporate, and finally freeze-dried to remove residual moisture to obtain a porous structured flexible self-healing anti-cracking material (MPSPU-x, x is the mass ratio of water to SPU).
[0007] The room temperature self-repairing flexible polyurea elastomer SSPU described in the present invention has the following structural formula:
[0008]
[0009] X and Y represent the percentage of each structural unit in the polymer, wherein n=50-80, X=0.3-0.5, Y=0.5-0.7, and X+Y=100%.
[0010] Preferably, the mass ratio of the room temperature self-healing flexible polyurea elastomer SSPU to the surfactant sodium dodecyl sulfate is 100:1.
[0011] Preferably, the mass volume ratio of the room temperature self-healing flexible polyurea elastomer SSPU to chloroform is 4 g:15-25 ml, more preferably 4 g:20 ml.
[0012] Preferably, when the mixture is dissolved in chloroform by stirring to obtain a viscous solution, the stirring time is more than 12 hours.
[0013] Preferably, when stirring until fully emulsified, the stirring speed is 500 to 1000 rpm and the stirring time is 20 to 30 minutes.
[0014] Preferably, the standing time is 1 to 2 hours.
[0015] Preferably, the mass ratio of water to the room temperature self-healing flexible polyurea elastomer SSPU is 100:100.
[0016] The present invention also provides a flexible self-repairing anti-cracking material with a porous structure prepared by the above preparation method.
[0017] Furthermore, the present invention provides the use of the above-mentioned porous structured flexible self-healing anti-crack material in the preparation of flexible stretchable devices.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) The present invention proposes for the first time a method for constructing a porous structure to change the fracture behavior of a material and improve the fracture energy of the material. This method transforms a soft but fragile self-healing material into a soft but tough self-healing material, thereby unprecedentedly improving the crack resistance. The method is achieved by manufacturing a closed microporous structure in the material using an inverse emulsion template technology. The presence of such closed micropores can change the direction of the crack, and eventually the crack deflects longitudinally, leaving a smooth longitudinal section, thereby eliminating the stress concentration perpendicular to the strain direction, so that the defective material can still achieve the same strain as the intact material.
[0020] (2) The porous structure of the flexible self-healing anti-crack material of the present invention not only improves the fracture energy of the material, but also does not lose the flexibility of the material, and abnormally further improves the flexibility of the material, achieving a synergistic improvement of the fracture energy and flexibility. The sample with defects has the same fracture strain as the intact sample, and the fracture energy can be as high as 100.86 kJ m -2 Compared with pure polyurea elastomer SSPU, the fracture energy is increased by 31.6 times. Compared with the polymer matrix SSPU without pore structure, the fracture energy is increased by 31.6 times (from 3.19 kJ m -2 Increased to 100.86 kJ m -2 ), while Young's modulus not only does not increase, but also significantly decreases by more than half (from 1.03MPa to 0.43MPa).
[0021] (3) The flexible self-healing anti-cracking material with a porous structure of the present invention has excellent room temperature self-healing ability and can completely repair mechanical properties within 12 hours at room temperature. The repair speed is twice as fast as that of the flexible self-healing polyurea elastomer SPU without a porous structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The fracture cross-section photo and SEM image of SSPU (a), as well as the photo of crack deflection of pre-notched MPSPU-100 during strain and the SEM image of the crack deflection point (b).
[0023] Figure 2This is the infrared spectrum of room temperature self-healing flexible polyurea elastomer SSPU.
[0024] Figure 3 This is the cross-sectional SEM image of the porous structured flexible self-healing anti-cracking material MPSPU-100.
[0025] Figure 4 This is the cross-sectional SEM image of the porous structured flexible self-healing anti-cracking material MPSPU-100-0.5.
[0026] Figure 5 This is the cross-sectional SEM image of the porous structured flexible self-healing anti-cracking material MPSPU-100-1.5.
[0027] Figure 6 Small-angle X-ray scattering spectrum of room-temperature self-healing flexible polyurea elastomer SSPU.
[0028] Figure 7 This is the room temperature repair stress-strain curve of room temperature self-healing flexible polyurea elastomer SSPU.
[0029] Figure 8 This is the room temperature repair stress-strain curve of the porous structured flexible self-healing tear-resistant material MPSPU-100.
[0030] Fig. 9 This is a photo of a complete MPSPU-100 sample with a microporous structure, which was stretched and deformed after being vertically cut with scissors. The notch did not penetrate horizontally, but deflected vertically, allowing the material to continue to stretch and deform to 1350% strain.
[0031] Fig.10 This is a photo of the tensile deformation of a pre-notched SSPU sample without a microporous structure. The notch quickly penetrates horizontally during the tensile deformation process, causing the material to break.
[0032] Fig.11 The stress-strain curves of the complete SSPU sample with dense and pore-free structure and the SSPU sample with a prefabricated 1 / 3 width notch in the width direction.
[0033] Fig.12 These are the stress-strain curves of the complete MPSPU-25 sample with a porous structure and the MPSPU-25 sample with a prefabricated 1 / 3 width notch in the width direction.
[0034] Fig.13 These are the stress-strain curves of the complete MPSPU-50 sample with a porous structure and the MPSPU-50 sample with a prefabricated 1 / 3 width notch in the width direction.
[0035] Fig.14These are the stress-strain curves of the complete MPSPU-100 sample with a porous structure and the MPSPU-100 sample with a prefabricated 1 / 3 width notch in the width direction.
[0036] Fig.15 These are the stress-strain curves of the complete MPSPU-150 sample with a porous structure and the MPSPU-150 sample with a prefabricated 1 / 3 width notch in the width direction.
[0037] Fig.16 This is a comparison chart of the Young's modulus of samples with different ratios of deionized water added during the preparation process.
[0038] Fig.17 A comparison of the fracture energy and fracture strain of each sample.
[0039] Fig.18 Stress-strain curves of original and multiple recycled MPSPU-100. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0041] The room temperature self-repairing flexible polyurea elastomer SSPU described in the present invention has been fully disclosed in the Chinese patent CN 117659330A previously applied for by the applicant, and its structural formula is as follows:
[0042]
[0043] X and Y represent the percentage of each structural unit in the polymer, wherein n=50-80, X=0.3-0.5, Y=0.5-0.7, and X+Y=100%.
[0044] The room temperature self-repairing flexible polyurea elastomer SSPU described in the present invention is prepared with reference to Chinese patent CN 117659330 A, specifically:
[0045] Step 1, dissolving aminopropyl-terminated polydimethylsiloxane (PDMS) in an organic solvent and stirring to obtain a PDMS solution;
[0046] Step 2, according to the molar ratio of trimethylhexamethylene diisocyanate (THI) to 4,4'-diisocyanato-3,3'-dimethylbiphenyl (DBI) of 7:3 to 5:5, trimethylhexamethylene diisocyanate and 4,4'-diisocyanato-3,3'-dimethylbiphenyl are mixed and dissolved in an organic solvent, and the mixture is added dropwise to the PDMS solution under a nitrogen atmosphere, and the mixture is heated to 55 to 65° C. and continuously stirred to obtain a polymer solution by reaction;
[0047] Step 3, pouring the polymer solution into a mold for molding, and drying to obtain a room temperature self-healing flexible polyurea elastomer SSPU.
[0048] In the following examples, the room temperature self-healing flexible polyurea elastomer SSPU is prepared by the following steps:
[0049] Step 1, dissolving 2 mmol of aminopropyl-terminated polydimethylsiloxane in 15 ml of chloroform and stirring to obtain a PDMS solution;
[0050] Step 2, 1.2 mmol of trimethylhexamethylene diisocyanate and 0.8 mmol of 4,4'-diisocyanato-3,3'-dimethylbiphenyl were mixed and dissolved in 15 ml of chloroform, and added dropwise to the PDMS solution under a nitrogen atmosphere, and stirred continuously at 60° C. for 6 hours to obtain a polymer solution;
[0051] Step 3, pouring the polymer solution into a mold for molding, and drying to obtain a room temperature self-healing flexible polyurea elastomer SSPU.
[0052] Example 1
[0053] The preparation method of a porous structured flexible self-repairing anti-cracking material comprises the following steps:
[0054] (1) 4 g of room temperature self-healing flexible polyurea elastomer SSPU and 0.04 g of SDS were dissolved in 20 ml of chloroform and stirred for more than 12 hours to obtain a viscous polymer solution, and then 2 ml of deionized water was added dropwise thereto, and a mechanical stirrer was used to continuously stir at a speed of 600 rpm for 30 minutes to form a uniform milky white viscous emulsion, which was then poured into a polytetrafluoroethylene mold;
[0055] (2) Dry at room temperature for 1 hour to evaporate the chloroform, then tear off the sample, pre-freeze at -50°C for 1 hour until the sample is completely frozen, and freeze-dry at 0°C for 3 days to remove residual moisture in the material to obtain a porous structured flexible self-healing anti-cracking material MPSPU-50.
[0056] Example 2
[0057] This embodiment is basically the same as Embodiment 1, except that the mass ratio of water to room temperature self-healing flexible polyurea elastomer SSPU is 100:100, that is, 4 ml of deionized water is added to obtain a porous structured flexible self-healing anti-cracking material MPSPU-100.
[0058] Example 3
[0059] This embodiment is basically the same as Embodiment 1, except that the mass ratio of water to room temperature self-healing flexible polyurea elastomer SSPU is 150:100, that is, 6 ml of deionized water is added to obtain a porous structured flexible self-healing anti-cracking material MPSPU-150.
[0060] Example 4
[0061] This embodiment is basically the same as Embodiment 1, except that the mass ratio of the room temperature self-healing flexible polyurea elastomer SSPU and the surfactant sodium dodecyl sulfate is 100:0.5, that is, 4g SSPU and 0.02g SDS are dissolved in 10ml chloroform to obtain a porous structured flexible self-healing anti-cracking material MPSPU-100-0.5.
[0062] Example 5
[0063] This embodiment is basically the same as Embodiment 1, except that the mass ratio of room temperature self-healing flexible polyurea elastomer SSPU and surfactant sodium dodecyl sulfate is 100:1.5, that is, 4g SSPU and 0.06g SDS are dissolved in 10ml chloroform to obtain a porous structured flexible self-healing anti-cracking material MPSPU-100-1.5.
[0064] like Figure 1 As shown in the figure, the MPSPU-100 sample with a microporous structure and the dense SSPU sample without a pore structure exhibit completely different crack resistance properties. The cracks in the SSPU will rapidly expand during the material strain process, causing the material to break and leaving a smooth cross-section perpendicular to the strain direction, while the cracks in the MPSPU-100 with a microporous structure will deflect in the strain direction, allowing the material to continue to deform, leaving a rough cross-section parallel to the strain direction.
[0065] like Figure 2 As shown, infrared spectra indicate that room temperature self-healing flexible polyurea elastomer SSPU was successfully synthesized.
[0066] like Figure 3 As shown, the scanning electron microscope image shows that there are widespread ellipsoidal closed micropores with a size of about 20 microns in the MPSPU-100 sample.
[0067] like Figure 4 As shown in the scanning electron microscope image, the MPSPU-100-0.5 sample is also full of ellipsoidal closed micropores, but the uniformity is better than Figure 3 The MPSPU-100 sample is slightly worse.
[0068] like Figure 5 As shown in the scanning electron microscope image, the MPSPU-100-1.5 sample is filled with denser ellipsoidal closed micropores, which are smaller than Figure 3 The MPSPU-100 sample is slightly smaller, and the micropores tend to be interconnected.
[0069] like Figure 6 As shown in Figure 3, the small-angle X-ray scattering curve of room temperature self-healing flexible polyurea elastomer SSPU shows that SSPU has a typical microphase separation structure.
[0070] like Figure 7 As shown, at room temperature, the dense SSPU with no pores can completely repair the mechanical properties within 24 hours.
[0071] like Figure 8 As shown, at room temperature, the porous structured flexible self-healing anti-cracking material MPSPU-100 can completely repair its mechanical properties within 12 hours.
[0072] like Fig. 9 As shown in the figure, the porous structure of the flexible self-healing anti-crack material can change the direction of the crack and has strong anti-crack ability. Even if the notch is sheared vertically during the tensile deformation of the material, the notch will not extend through, but will deflect longitudinally, leaving a straight cross section, allowing the material to continue to stretch and deform to 1350% strain.
[0073] like Fig.10 As shown, the dense SSPU sample without a pore structure does not have the ability to resist cracks, and the sample with a pre-notched structure breaks rapidly during the strain process.
[0074] like Figure 11-15 , Fig.17 As shown in the figure, with the increase of deionized water content during the preparation process, the tear strain of the porous structured flexible self-healing anti-cracking material increased from 104.42% to 1389.42%, and the fracture energy increased from 3.19 kJ m -2 Increased to 100.86 kJ m -2 MPSPU-100-0.5 in Example 4 and MPSPU-100-1.5 in Example 5 exhibit similar mechanical properties and crack resistance to MPSPU-100. This indicates that when the pore structure can exist stably, the volume ratio of the pore structure plays a leading role in improving the material's crack resistance.
[0075] like Fig.16 As shown, with the increase of deionized water content during the preparation process, the Young's modulus of the porous structured flexible self-healing anti-cracking material gradually decreases, that is, the flexibility gradually increases.
[0076] like Fig.18 As shown, unlike other composite materials with complex filling structures, this porous structured flexible self-healing and crack-resistant material can be repeatedly recycled and molded without changing the performance of the sample.
[0077] Comparative Example 1
[0078] (1) Dissolve 4 g SPU and 0.04 g SDS in 10 ml chloroform and stir for more than 12 hours to obtain a viscous polymer solution. Pour the solution directly into a polytetrafluoroethylene mold without adding deionized water;
[0079] (2) Dry at room temperature for 1 hour to volatilize chloroform, and continue drying at 60°C for 6 hours to completely remove the solvent. Then, tear off the sample and store it in a desiccator to obtain a room temperature self-healing polyurea elastomer SPU-SDS that does not contain a microporous structure but still disperses an emulsifier, sodium dodecyl sulfate.
[0080] Comparative Example 2
[0081] (1) Dissolve 4 g of SPU and 0.04 g of SDS in 10 ml of chloroform and stir for more than 12 hours to obtain a viscous polymer solution, add 1 ml of deionized water dropwise thereto, and stir at a speed of 600 rpm for 30 minutes with a mechanical stirrer until a uniform milky white viscous emulsion is obtained, which is then poured into a polytetrafluoroethylene mold;
[0082] (2) Dry at room temperature for 1 hour to evaporate the chloroform, then tear off the sample, pre-freeze at -50°C for 1 hour until the sample is completely frozen, and freeze-dry at 0°C for 3 days to remove residual moisture in the material to obtain a porous structured flexible self-healing anti-cracking material MPSPU-25.
[0083] Comparative Example 3
[0084] (1) Dissolve 4 g of SSPU in 20 ml of chloroform without adding SDS, and stir thoroughly for more than 12 hours to obtain a viscous polymer solution. Add 4 ml of deionized water dropwise into the solution, stir continuously at 600 rpm for 30 minutes with a mechanical stirrer, and then pour into a polytetrafluoroethylene mold.
[0085] (2) Dry at room temperature for 1 hour to evaporate the chloroform, then tear off the sample, pre-freeze at -50°C for 1 hour until the sample is completely frozen, and freeze-dry at 0°C for 3 days to remove residual moisture in the material to obtain MPSPU-100-0.
[0086] During the preparation process, it was found that the droplets in Comparative Example 3 could not be stably dispersed to obtain a stable emulsion, and thus a uniform porous structure material could not be prepared.
[0087] Comparative Example 4
[0088] (1) Dissolve 4 g SSPU and 0.08 g SDS in 20 ml chloroform and stir for more than 12 hours to obtain a viscous polymer solution, add 4 ml deionized water dropwise thereto, and stir at a speed of 600 rpm for 30 minutes with a mechanical stirrer until a uniform milky white viscous emulsion is obtained, which is then poured into a polytetrafluoroethylene mold;
[0089] (2) Dry at room temperature for 1 hour to evaporate the chloroform, then tear off the sample, pre-freeze at -50°C for 1 hour until the sample is completely frozen, and freeze-dry at 0°C for 3 days to remove residual moisture in the material to obtain a porous structured flexible self-healing anti-cracking material MPSPU-100-2.
[0090] The emulsion obtained in Comparative Example 4 is extremely dense and creamy. When chloroform is volatilized, the organic solvent evaporates slowly, and the water in the emulsion is difficult to retain during the long volatilization process, and a uniform porous structure material cannot be prepared.
[0091] like Fig.11 As shown, when it does not contain a porous structure, SPU-SDS exhibits poor crack resistance similar to that of SPU, indicating that the crack resistance of the porous structured flexible self-healing anti-crack material MPSPU-x comes from the microporous structure rather than the emulsifier sodium dodecyl sulfate.
[0092] like Fig.12 As shown, when the content of deionized water added during the preparation process is too little, that is, the pore structure content in the final sample is too low, the material's crack resistance is limited, indicating that in this toughening method, sufficient pore structure is required to induce crack deflection.
Claims
1. A method for preparing a porous structured flexible self-repairing anti-cracking material, characterized in that: The specific steps are as follows: The room temperature self-repairing flexible polyurea elastomer SSPU and the surfactant sodium dodecyl sulfate are stirred and dissolved in chloroform at a mass ratio of 100:0.5~1.5 to obtain a viscous solution, and then water is added dropwise to the viscous solution at a mass ratio of water to the room temperature self-repairing flexible polyurea elastomer SSPU of 50~150:100, and stirred until fully emulsified, and then the emulsion is poured into a mold, and allowed to stand at room temperature to volatilize the chloroform, and finally freeze-dried to remove residual moisture to obtain a porous structure of a flexible self-repairing anti-cracking material. The structural formula of the room temperature self-repairing flexible polyurea elastomer SSPU is as follows: , X and Y represent the percentage of each structural unit in the polymer, where n=50~80, X=0.3~0.5, Y=0.5~0.7, and X+Y=100%.
2. The preparation method according to claim 1, characterized in that: The mass ratio of room temperature self-healing flexible polyurea elastomer SSPU and surfactant sodium dodecyl sulfate is 100:
1.
3. The preparation method according to claim 1, characterized in that: The mass volume ratio of room temperature self-healing flexible polyurea elastomer SSPU and chloroform is 4g:15~25ml.
4. The preparation method according to claim 1, characterized in that: The mass volume ratio of room temperature self-healing flexible polyurea elastomer SSPU and chloroform is 4g:20ml.
5. The preparation method according to claim 1, characterized in that: When the solution is dissolved in chloroform by stirring to obtain a viscous solution, the stirring time is more than 12 hours.
6. The preparation method according to claim 1, characterized in that: When stirring until fully emulsified, the stirring speed is 500~1000 rpm and the stirring time is 20~30 minutes.
7. The preparation method according to claim 1, characterized in that: The standing time is 1 to 2 hours.
8. The preparation method according to claim 1, characterized in that: The mass ratio of water to room temperature self-healing flexible polyurea elastomer SSPU is 100:
100.
9. A porous flexible self-healing anti-cracking material prepared according to the preparation method of any one of claims 1 to 8.
10. Use of the porous structured flexible self-healing anti-cracking material according to claim 9 in the preparation of flexible stretchable devices.
Citation Information
Patent Citations
Rapid exchange transcatheter valve delivery system
US20210121291A1
Preparation method of microcapsules for self-repairing polymeric porous material
CN109651549A
High-performance self-repairing polyurea and preparation method thereof
CN114685756A
Self-repairing flexible bionic composite material with high tear resistance and preparation method thereof
CN117659330A